A Test of word-finding abilities in children (hindi) - Shipra K.N (Journal of All India Institute of Speech and Hearing, 1970)
There has been a dianostic gap in the assessment of wordfinding disorders in children. Although professionals have long been aware of this expressivelanguage disorders in children (Johnson & Myklebust 1967; Denckla & Rudel, 1974; Wiig & Semel, 1976), until recently there has been no standardiseddiagnostic measure and assessment. This gap has been particularly evident to professionals responsible for providing diagnostic and remedial services tochildren with linguistic disorders. As Weigel-Grump & Dennis (1986) state